Mode-Counteraction Based Self-Decoupling in Circularly Polarized MIMO Microstrip Patch Array - Lai, Qi Xuan; Pan, Yong Mei; Zheng, Shao Yong (IEEE transactions on antennas and propagation, 2022)
A mode-counteraction-based self-decoupling method is proposed for the circularly polarized (CP) multi-input multi-output (MIMO) microstrip patch antenna (MPA) array. The array simply consists of two identical diagonal-fed rectangular MPAs, without any extra decoupling structure. It is found that by properly adjusting the patch dimensions and feeding positions, the orthogonal TM1, 0 and TM0, 1 modes can be simultaneously excited in the active MPA to generate the CP field. Meanwhile, the coupled E -fields of the two modes in the adjacent passive MPA can counteract each other, generating a null-field region. When the feeding probe of the passive MPA is placed within the null-field region, no signal can be received at the port, and consequently, an extremely low mutual coupling of −59.4 dB is achieved, without scarifying any other radiation performance of the MPA. In addition, this self-decoupling method is also applicable to other types of MPA arrays and four-element MPA arrays, exhibiting great versatility and extensibility.